Optimizing The Position of The Founder Agreement In Establishing A Start-Up Company In The Form Of A Limited Liability Company: Legal Analysis Of Limited Liability Companies - Reihania Arta; Hanif Nur Widhiyanti; Patricia Audrey Ruslijanto (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In Indonesia, the phenomenon of start-up companies is widely embraced and positively received in society. One notable start-up that originated in Indonesia has had a significant impact on the business landscape. However, there is currently no specific legislation governing start-up companies in Indonesia. Consequently, the establishment of start-up businesses is not explicitly regulated regarding their legal structure. Nevertheless, a majority of digital start-up companies in Indonesia choose to be established as Limited Liability Companies (Limited Liability Company), primarily due to the need for capital injection from investors during the establishment process. This preference is driven by the trust investors place in companies with legal legitimacy and recognition. The Founders Agreement represents the initial commitment of each founder to establish the company. By documenting the Founders Agreement in writing, founders are expected to adhere to the agreed-upon terms and face sanctions in case of violations, preventing potential betrayals. However, in the context of start-up company establishment, the concept of a Founders Agreement is not explicitly recognized in the Indonesian Company Law (Limited Liability Company Law). Given the significance of the Founders Agreement, which serves as a distinctive feature of start-up companies, this research aims to explore its role in the establishment of start-up companies and the existence of founders in the form of limited liability companies. The urgency of the Founders Agreement lies in its preventive function against internal conflicts among the founders of start-up companies, thereby mitigating risks that may arise. Therefore, this study will examine the position of the Founders Agreement in the establishment of start-up companies, particularly those structured as limited liability companies